Investigating Students’ Difficulties in Translating English Academic Texts into Indonesian Using Photovoice - Praptika, Diana; Rokhuma, Chubbi Millatina (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
Translation is the process of transferring the meaning of a text from the source language (SL) to the target language (TL). However, many students experience difficulties in the translation process. This study aimed to reveal the difficulties faced by students in translating English academic texts especially English journal articles into Indonesian and the strategies they use to overcome their difficulties. It investigated students' experiences using qualitative approach with photovoice as the research design. The data collection was carried out by using photographs as well as semi-structured interviews. The gathered data were then analyzed by following steps of thematic analysis. This type of analysis helped the researcher identify students' difficulties and the translation strategies they use through their photos and descriptions. The results showed that the students have difficulties in pragmatics, cultural, and textual. In solving these difficulties, the students used some strategies including transference, naturalization, cultural equivalent, descriptive equivalent, synonymy, through translation, shift or transposition, reduction, paraphrase, couplets, and addition. The result of this research can be used by educators as a reference to identify the difficulties faced by their students early in translating academic texts. Therefore, they can guide their students to find the right strategies by using different types of difficulties.